(untitled) (Faridpur Medical College Journal, 2018)
Low birth weight (LBW, <2500g) is an important indicator of reproductive health and general health status of population. LBW is considered as the single most important predictor of infant mortality, especially of deaths within the first month of life. This is a prospective case control study carried out in the Department of Obstetrics & Gynaecolgy, Faridpur Medical College Hospital, Faridpur, during the period of August 2015 to July 2016 to find out the risk factors associated with low birth weight babies and to know modifiable risk factors. Total 300 samples were included in this study. All pregnant women who delivered a LBW baby during one year of study period were selected. One hundred mothers who delivered babies having birth weight <2500 gram were selected as cases and 200 mothers who delivered babies having birth weight 2500 gram and above were taken as control. This study shows most frequent maternal age group was 18-25 years in case group and 26-35 years in control group. Fifty four percent were female and 46% were male babies in case group where as 39% were female and 61% were male babies in control group. In LBW babies mothers, having regular antenatal care were only 23.8%. Maternal factors including maternal height, maternal weight, pre-eclampsia, PROM, chronic hypertension & PPH, heart disease and DM were associated with low birth weight. Fifty six percent mothers had average food intake and 34% had poor food intake in mothers of low birth weight baby. The status of antenatal check-up and poor socio economic condition also strongly influence birth weight of baby. There is a need for national prospective research project to study the low birth weight problem at the national level. Faridpur Med. Coll. J. Jan 2018;13(1): 31-34